Semantic Association of Jihad: Indonesian Muslim Students’ Perspectives - Nur Latifah; Akhmad Muzakki; Sofiatul Karimah (Athena: Journal of Social, Culture and Society, 2023)
The findings show that the students’ view on Jihad is not merely identical to fighting but also the application of Jihad, which varies. It has a wide spectrum as long as its purpose and still in the religious morality frame. Spreading Rahmatan (affection) concept and The word jihad, which mentioned in the Qur'an about 35 times, including its derivations, has often been understood only at the scriptural level, detached from its contexts. As a result, jihad has been assumed to be a specific act of violence, such as terrorism and radicalism. This article aims to explain the concept of jihad in Islam from the perspective of Indonesian Muslim students at Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, and to explore the factors that influence their understanding of jihad. This study adopts a semantic approach to the teaching of jihad in the Qur'an, contextualizing it with the current situation. The findings show that the students' view of jihad is not limited to physical fighting, but also includes a wide range of other applications, as long as they are motivated by religious morality. The moral and spiritual values implicit in jihad include spreading the concept of rahmahan (affection) and promoting peace of life and spiritual values